Introduction to Industrial Engineering - Abdul Talib Bon; Mohamed Ismail Hj Pakir Mohamed; Ahmad Nur Aizat Ahmad (Penerbit UTHM, 2023)
This book was written for undergraduate management students taking the Introduction to Industrial Engineering course. The chapters in this book provide an overview of the profession as well as essential fundamental knowledge that management students may utilize to execute IE approaches in the operation management in the manufacturing and service sectors. The book contains several features to enhance student learning of IE technique: The opening chapter highlight how it all begin.